Ginger relieves intestinal hypersensitivity of diarrhea predominant irritable bowel syndrome by inhibiting proinflammatory reaction - Changrong Zhang; Yongquan Huang; Peiwu Li; Xinlin Chen; Fengbin Liu; Qiuke Hou (BMC, 2020)
Abstract Background Ginger or ginger extracts have been used in traditional medicine relieve pain caused by diarrhea predominant irritable bowel syndrome (IBS-D), but few data exists about its effectiveness. This present study was to validate the effect of ginger on visceral pain, and to further explore the possible underlying mechanism by which ginger is used to relieve IBS-D intestinal hypersensitivity. Methods First, the IBS-D rat model was established by chemical stimulation and acute and chronic pressure stimulation. Then, different dose of ginger were administrated to IBS-D rats and evaluate the defecation frequency, fecal water content (FWC) and abdominal withdrawal reflex (AWR) scores in IBS-D rats. Further, the IBS-D rats were sacrificed to collecte the colonic tissues to evaluate the effect of ginger administration on its pathology and changes of pro-inflammatory factors, and changes of NF-κB pathway. Second, the ginger was taken to HPLC analysis and 6-gingerol was choosen to further experiment. Then, IBS-D rats were treated with different dose of 6-gingerol, and the behavioral evaluation were to evaluate the effect of 6-gingerol on IBS-D rats. Further, colonic epithelial cells (CECs) were collectted and to evaluate the effect of 6-gingerol on the expression of inflammatory factors and changes of NF-κB pathway. Results The IBS-D rat model was successfully established by chemical stimulation and acute and chronic pressure stimulation. And ginger treatment significantly reduced the defecation frequency, fecal water content and AWR scores in IBS-D rats. Histopathological analysis showed that ginger treatment can significantly reduce colonic edema and promote the recovery of inflammation in IBS-D rats, and the effect is equivalent to rifaximin. Elisa and RT-qPCR showed that ginger inhibited the expression of proinflammatory factors (TNF-α, IL-6, iNOS) in IBS-D rats. Western blot showed IkBα was up-regulated while p-p65 was inhibited under ginger treatment. HPLC analysis showed that 6-gingerol was the main component of ginger, which could improve clinical symptoms in IBS-D rats. Western blot and RT-qPCR showed that 6-gingerol inhibited the expression of proinflammatory factors (TNF-α, IL-6, iNOS) in CECs, and inhibition of IκBα degradation and phosphorylation of p65 involved in NF-κB pathway. Conclusion Ginger and ginger extract could relieve intestinal hypersensitivity of IBS-D by inhibiting proinflammatory response.